Movement of Cryptosporidium parvum Oocysts through Soils without Preferential Pathways: Exploratory Test - Darnault, Christophe J. G.; Peng, Zhenyang; Yu, Chan; Li, Biting; Jacobson, Astrid R.; Baveye, Philippe C. (Frontiers in Environmental Science, 2017)
Groundwater contamination by oocysts of the waterborne pathogen Cryptosporidium parvum is a significant cause of animal and human disease worldwide. Although research has been undertaken in the past to determine how specific physical and chemical properties of soils affect the risk of groundwater contamination by C. parvum, there is as yetno clear conclusion concerning the range of mobility of C. parvum that one should expect in field soils. In this context, the key objective of this research was to determine the magnitude of C. parvum transport in a number of soils, under conditions in which fast and preferential transport has been successfully prevented. C. parvum oocysts were applied at the surface of different soils and subjected to artificial rainfall. Apparently for the first time, quantitative PCR was used to detect and enumerate oocysts in the soil columns and in the leachates. The transport of oocysts by infiltrating water, and the considerable retention of oocysts in soil was demonstrated for all soils, although differences in the degree of transport were observed with soils of different types. More oocysts were found in leachates from sandy loam soils than in leachates from loamy sand soils and the retention of oocysts in different soils did not significantly differ. The interaction of various processes of the hydrologic system and biogeochemical mechanisms contributed to the transport of oocysts through the soil matrix. Results suggest that the interplay of clay, organic matter, and Ca2+ facilitates and mediates the transfer of organic matter from mineral surfaces to oocysts surface, resulting in the enhanced breakthrough of oocysts through matrices of sandy loam soils compared to those of loamy sand soils. Although the number of occysts that penetrate the soil matrix account for only a small percentage of initial inputs, they still pose a significant threat to human health, especially in groundwater systems with a water table not too distant from the soil surface.